Monitoring, sanctions and front-loading of job search in a non-stationary model - Bart Cockx; Muriel Dejemeppe; Andrey Launov; Bruno Van der Linden (Institute for the Study of Labor (IZA), 2011)
We develop and estimate a non-stationary job search model to evaluate a scheme that monitors job search effort and sanctions insured unemployed whose effort is deemed insufficient. The model reveals that such schemes provide incentives to the unemployed to front-load search effort prior to monitoring. This causes the job finding rate to increase above the post sanction level. After validating the model both internally and externally, we conclude that the scheme is effective in raising the job finding rate with minor wage losses. A basic cost-benefit analysis demonstrates that welfare losses for the unemployed are compensated by net efficiency gains for public authorities and society.
urn:nbn:de:101:1-201201103126
Keywords: J64; J68; C41; 330; monitoring; sanctions; non-stationary job search; unemployment benefits; structural estimation; Arbeitsuche; Kontrolle; Arbeitslosenversicherung; Strafe; Kosten-Nutzen-Analyse; Wohlfahrtsanalyse; Theorie